Discussing Style with Ghosts: Aesthetics and Haunting in the Age of Historicism. Issue 1 (2nd January 2021) - Blunk, Julian
Abstract: In the age of historicism, stylistic choices were simultaneously projections of identity. At the same time, the idea that the recovery of a historic style would also resurrect the "spirit" of a particular era represented both the supreme hope and the greatest fear of historicism. Ghosts therefore acted as figures of memory who were summoned as correctives of current conceptions of history, and who call attention to their own (often forgotten) stories. The neo-styles themselves were either discredited or legitimised as the undead ghosts of their reference styles. With reference to Johann Wolfgang von Goethe's "Von Deutscher Baukunst" (On German Architecture) ( Berliner Ausgabe. Kunsttheoretische Schriften und Übersetzungen 20 ([1772] 1960): 28–38) and other texts, the article demonstrates that (metaphorical) consultations with ghosts represented attempts to close gaps in the historical research while "clarifying" unresolved questions of cultural inheritance.